Maintaining Employees’ Morality to Improve Internal Control in the Sharia Microfinance Institution - Hasan Mukhibad (LP2M - Universitas Islam Negeri (UIN) Walisongo, 2017)
Problems of fraud committed by a company’s internal party are hitherto still problematic to figure out, including in sharia microfinance institutions. This research examines the benefit of maintaining employees’ morality for the improvement of internal control in sharia microfinance institutions. The object of this research is Anda BMT (sharia microfinance institution in Indonesia). The research uses a qualitative method. The data were obtained by interviewing the managers and twenty employees, and also through field observations for four months. The result of this research shows that the management needs to improve the employees’ morality as it is the key element to prevent fraud act. The efforts made to improve the employees’ morality are like praying together, joining a program of Islamic study once a week, and targeting all employees to read the Quran at least One Day One Juz (ODOJ). Islamic religious activities should be applied to sharia financial institutions in order to improve the employees’ morality and to diminish the act of fraud. It is because the employees who properly carry out Islamic religious activities may reduce the potency of fraud.